Maximum Utilization of Cocopeat Waste as a Substitute Material for Fine Aggregates On Paving Blocks Was Engineered - Dwi Kurniati (Civilla : Jurnal Teknik Sipil Universitas Islam Lamongan, 2022)
Waste utilization can be done in various ways, one of the wastes used in this study is cocopeat waste. Cocopeat is a coconut pulp powder commonly used to cultivate plants. But this time, this waste is processed into a paving block mixture. The goal is to find out the strong press and quality resulting from the utilization of cocopeat in the manufacture of paving blocks. The method used refers to SNI 03-0691-1996. The first step of coconut pulp is destroyed, then used as a paving block mixture as a sand substitution. Cocopeat substitution paving block testing with percentages of 0.6%, 0.8%, 1%, 1.2%, 1.4%, 1.6%, 1.8%, 2%, and 2.2%. The total compressed strong test sample conducted amounted to 90 pieces with a test object size of 150x100x60 mm. The average compressive force generated by each percentage is 0.6% of the 14.71 MPa, 0.8% of 13.56 MPa, 1% of 13.76 MPa, 1.2% of 14.74 MPa, 1.4% of 14.13 MPa, 1.6% of 13.08 MPa, 1.8% of 12.43 MPa, 2% of 13.22 MPa, and 2.2% of 10.33 MPa. In conclusion from the test results, cocopeat substitution paving blocks have an average grade C quality that can be used for pedestrians, so this mixture can be recommended.